Analisis Kebutuhan Bahan Ajar Interaktif Berbasis Augmented Reality (AR) Pada Topik Elektrolisis - Ahmad Fauzi Syahputra Yani (KATALIS: Jurnal Penelitian Kimia dan Pendidikan Kimia, 2023)
Teaching materials are an important aspect of the implementation of the teaching and learning process. In the post-covid-19 era, students are used to learning not only during class hours but also outside class hours. Teaching materials that can be used in this case are digital-based teaching materials. This research aims to analyze students' needs for interactive teaching materials that integrate augmented reality technology. This type of teaching material is digital teaching material that can be installed on students' gadgets such as smartphones and laptops. Students can access and learn anywhere and anytime. This research belongs to the realm of mixed methods which combines quantitative and qualitative research. Based on the results of a closed questionnaire filled out by chemistry education students who carried out PLP in Langsa city and the students showed an average percentage of 76.32%. This percentage is included in the mostly needy category. These results are supported by the results of an open questionnaire distributed to chemistry education students who carry out PLP in Langsa city and students. The results of an open questionnaire filled out by chemistry education students who carry out PLP in Langsa city and students also provide information that studying the reactions that occur at the cathode and anode is one of the main problems in studying electrolysis. This is because students feel that this topic is something abstract, so teaching materials are needed that accommodate this topic to make it more real in the eyes of students. In this case, augmented reality technology is an alternative technology that can be used.